1987
DOI: 10.1063/1.866513
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of vorticity and scalar gradient with strain rate in simulated Navier–Stokes turbulence

Abstract: Articles you may be interested inA framework for epistemic uncertainty quantification of turbulent scalar flux models for Reynolds-averaged Navier-Stokes simulations Phys. Fluids 25, 055105 (2013);

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

126
577
6

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 732 publications
(715 citation statements)
references
References 14 publications
126
577
6
Order By: Relevance
“…Recall that, in turbulence, the vorticity tends to be aligned withê 2 (Ashurst et al 1987). It would then be expected that the conditional average of the tumbling rate on p ·ê 2 (figure 11(b)) would share some similarity with the conditional average on p ·ω (figure 9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recall that, in turbulence, the vorticity tends to be aligned withê 2 (Ashurst et al 1987). It would then be expected that the conditional average of the tumbling rate on p ·ê 2 (figure 11(b)) would share some similarity with the conditional average on p ·ω (figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…Intuitively, one would expect that the vorticityω would tend to align with the most extensional eigenvector,ê 1 . But, in general, vorticity is preferentially aligned with the intermediate eigenvectorê 2 (Ashurst et al 1987). We show the PDFs of the cosine of the angle betweenω and theê i in figure 7 for our measured velocity gradients and for the direct numerical simulation.…”
Section: Alignment Between Vorticity and Strain Rate Tensormentioning
confidence: 99%
“…See f i g u r e 1 . The r e s u l t i n g mean temperature (chemical product) p r o f i l e t h a t peaks i n t h e i n t e r i o r of the r e a c t i o n zone is more a consequence of the v a r i a t i o n of the f r a c t i o n of t h e time a given f i x e d point is v i s i t e d by t h e h o t l a r g e s c a l e c o r e s (duty c y c l e ) , r a t h e r than t h e v a r i a t i o n of the temperature f i e l d w i t h i n a core.…”
Section: N O T H E R Words While Having T H E C O R R E C T F L U mentioning
confidence: 99%
“…In reality they are pseudo-3D in nature as they are composed of 2D flows superimposed on a 3D vorticity free strain field, a fact exploited by Lundgren in his transformation [2]. Depending on whether a tube or shear layer symmetry has been chosen, corresponding to uni-axial or bi-axial strain [3], they have the properties that the vorticity ω ω ω firstly lies respectively either along the axis of the tube or in the plane of the layer and secondly that it aligns with an eigenvector of the strain matrix S. While numerical simulations [10,11] and experiments [12] have shown that, in a spatially averaged sense, alignment of the vorticity vector ω ω ω with the intermediate eigenvector of S is favoured (for a list of references see [13]), it is clear that local vorticity accumulation and alignment processes are more complicated than this [14,15]. For instance, the solution for the Burgers vortex has the drawback that it is stretched by a strain field that is decoupled from the flow around it and that its vorticity is unidirectional [1][2][3].…”
Section: Introductionmentioning
confidence: 99%